(untitled) (Journal of Informatics and Mathematical Sciences, 2014)
Let N_0 be the set of all non-negative integers and P(N_0) be its power set. An integer additive set-indexer (IASI) is dened as an injective function f:V(G)→ P(N_0) such that the induced function f^+:E(G)→ P(N_0) defined by f^+(uv) = f(u) + f(v) is also injective, where f(u) + f(v) is the sumset of f(u) and f(v). An IASI f is said to be a weak IASI if |f^+(uv)| = (|f(u)|,|f(v)|) uv E(G). In this paper, we study the admissibility of weak IASI by certain graph products of two weak IASI graphs.